Chemical constituents of ethyl acetate extract of Lepisanthes rubiginosa collected in Phu Loc district, Thua Thien - Hue province. - Ninh, Phạm Thị; Phương Thảo, Trần Thị; Lộc, Trần Văn; Dung, Nguyễn Thị; Cẩm, Đỗ Xuân; Sung, Trần Văn (Vietnam Journal of Chemistry, 2017)
From the ethyl acetate extract of the plant Lepisanthes rubiginosa collected on the beach in Phú Lộc district, Thua Thien- Hue province, five compounds: lupeol, diosmetin, heptadecanoic acid, β-sitosterol and β-sitosterol-3-O-β-D-glucopyranoside have been isolated. Their structures were  determined based on the analysis of the FT- IR, MS, NMR spectra (1D and 2D) and comparison with the literatures. These compounds have been isolated for the first time from Lepisanthes rubiginosa. Keywords. Lepisanthes rubiginosa, Sapindaceae, lupeol, diosmetin, heptadecanoic acid.